In situ atomic force microscopy (AFM) investigation of kaolinite dissolution in highly caustic environments - Chaliha, D.; Gomes, J.F.; Smith, P.; Jones, Franca (ROYAL SOC CHEMISTRY, 2022)
Clays are a common component of bauxite, and reactive silica, in the form of clays, is an important precursor of desilication products. Despite this, the behaviour of clays in highly caustic environments is not well investigated and this is due to the nature of the corrosive environment as well as the temperatures normally encountered (normally ∼90 °C for the desilication process unit). Atomic force microscopy has been used in this work to image the dissolution of kaolinite in situ at various temperatures (25-55 °C) and in different solutions (pure caustic, synthetic Bayer liquor and synthetic Bayer liquor with added waterglass). This work has shown that the dissolution behaviour is similar in all these solutions. Little impact of temperature is expected on dissolved silicate in the range studied though some of the results may be impacted by the batch nature of the set-up. In the synthetic Bayer liquor, due to the aluminate present, it can also be concluded that the aluminate sheet of the kaolinite should dissolve more slowly than the silicate sheet. The dissolution of kaolinite steps in the Bayer liquor is slightly faster compared to the pure caustic case. In addition, there is a fast and slow dissolution direction for the steps observed on kaolinite. However, the size of the particles or features also changes suggesting that edges are the fastest features to dissolve and this is supported by the initial formation of aluminosilicates at kaolinite edges.